Post-harvest technological treatments of pomegranate and preparation of derived products - Artés F.; Tomás-Barberán F.A. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
During the last few years, the activity in research and development on pomegranate fruit has aimed at the application of new post-harvest storage technologies to extend the storage life of pomegranates, keeping the original quality of the freshly harvested fruits. In this way research has focused to the application of controlled atmospheres, the use of modified atmosphere packaging in polymeric films and the application of thermal treatments during the refrigerated storage. These technological treatments were applied to alleviate chilling injury symptoms which occur during the storage of pomegranates below 5 degrees C. Although the industrial processing of pomegranate is still scarce, research on the development of new products such as minimally processed seeds, jams, juices and jellies has been carried out. This new sector of pomegranate industrial processing will allow the use of fruits with low commercial quality fruits.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)